The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/j.2042-7158.1998.tb03317.x
|View full text |Cite
|
Sign up to set email alerts
|

Different Absorption Profiles of Deramciclane in Man and in Dog

Abstract: We have studied the dog model for predicting the oral absorption of deramciclane, a novel anxiolytic compound, as a model acid-labile drug. The absorption profile of deramciclane was studied in man and beagle dogs after administration of conventional capsules and enteric coated tablets. Absorption in dogs pretreated with pentagastrin or saline was also studied after administration of conventional capsules. The in-vitro stability of deramciclane was determined over the pH range 1.2-6.0. The rate of degradation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Beagle dogs have frequently been used as a surrogate to human for the study of drug absorption because of their ability to ingest human‐scale dosage forms and their ease of handling. However, significant differences exist between the oral bioavailability observed in dogs and that observed in humans 16,17. Gastric pH in humans has been evaluated using a variety of methodologies, including orogastric or nasogastric intubation and aspiration, direct measurement via a pH probe in the stomach, and radiotelemetry (e.g., Heidelberg capsule).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beagle dogs have frequently been used as a surrogate to human for the study of drug absorption because of their ability to ingest human‐scale dosage forms and their ease of handling. However, significant differences exist between the oral bioavailability observed in dogs and that observed in humans 16,17. Gastric pH in humans has been evaluated using a variety of methodologies, including orogastric or nasogastric intubation and aspiration, direct measurement via a pH probe in the stomach, and radiotelemetry (e.g., Heidelberg capsule).…”
Section: Introductionmentioning
confidence: 99%
“…However, significant differences exist between the oral bioavailability observed in dogs and that observed in humans. 16,17 Gastric pH in humans has been evaluated using a variety of methodologies, including orogastric or nasogastric intubation and aspiration, direct measurement via a pH probe in the stomach, and radiotelemetry (e.g., Heidelberg capsule). Regardless of the method used, fasting gastric pH in humans has been reported to be less than 3.…”
Section: Introductionmentioning
confidence: 99%
“…Formulation 5: Formulation 4 administered to dogs that were pre-treated orally with 4 ml/kg 0.1 N HCl. * = Significantly different from all other treatment groups, p50.01, one-way ANOVA with Bonferroni multiple comparisons post-test co-workers [18]. To avoid the ambiguity of this indirect approach in the present investigation, the pH of the fasted dog stomach was manipulated directly.…”
Section: Discussionmentioning
confidence: 98%
“…To attempt to normalize the pH of the fasted dog stomach to that of other preclinical species and of human, various investigators have attempted to artificially decrease the dog stomach pH. Knupp and colleagues [17] successfully pretreated dogs with pentagastrin to stimulate HCl release, while the same technique proved variable and unsuccessful in a study by Kanerva and co-workers [18]. To avoid the ambiguity of this indirect approach in the present investigation, the pH of the fasted dog stomach was manipulated directly.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Previously published pharmacokinetic studies in several different species, including man, have shown extensive metabolism, with cleavage of the side chain the major metabolic pathway. [5][6][7][8][9][10] The resulting metabolite and derivatives show increased distribution and significant plasma levels for a longer biological half-life than the parent compound. 11,12 Two tritium labelled forms of deramciclane were required with the label in the camphor skeleton, ([3-3 H]deramciclane (3)) and the side chain ([2-dimethylamino-[2-3 H]ethoxy]deramciclane (9)) for in vitro and in vivo studies to further investigate various aspects of the metabolism and pharmacokinetics of deramciclane.…”
Section: Introductionmentioning
confidence: 99%